2014
DOI: 10.2147/ndt.s69652
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural abnormalities in behavior therapy-resistant obsessive-compulsive disorder revealed by voxel-based morphometry

Abstract: BackgroundAlthough several functional imaging studies have demonstrated that behavior therapy (BT) modifies the neural circuits involved in the pathogenesis of obsessive-compulsive disorder (OCD), the structural abnormalities underlying BT-resistant OCD remain unknown.MethodsIn this study, we examined the existence of regional structural abnormalities in both the gray matter and the white matter of patients with OCD at baseline using voxel-based morphometry in responders (n=24) and nonresponders (n=15) to subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…3745 The reduced connections in this pivotal region impair information communication ability, thereby impairing the modulation of emotion, cognitive, and memory processing and leading to more complex and more serious obsessive-compulsive symptoms. 9,33,35,4654 Overall, our findings suggest that decreased gFCD may be a specific brain-pathological characteristic of TROCD. The impaired information communication processing caused by decreased gFCD in the left middle temporal gyrus may cause OCD to become refractory to treatment.…”
Section: Discussionmentioning
confidence: 52%
“…3745 The reduced connections in this pivotal region impair information communication ability, thereby impairing the modulation of emotion, cognitive, and memory processing and leading to more complex and more serious obsessive-compulsive symptoms. 9,33,35,4654 Overall, our findings suggest that decreased gFCD may be a specific brain-pathological characteristic of TROCD. The impaired information communication processing caused by decreased gFCD in the left middle temporal gyrus may cause OCD to become refractory to treatment.…”
Section: Discussionmentioning
confidence: 52%
“…While recent studies showed that treatment response might improve with diffusion magnetic resonance imaging (MRI) guided DBS targeting ( Baldermann et al, 2019 , Coenen et al, 2017 , Liebrand et al, 2019 ), it is unlikely that all patients will become responders in the future. Since OCD has been associated with various structural brain abnormalities ( Boedhoe et al, 2017 , Gan et al, 2017 , Hashimoto et al, 2014 ), differences in (individual) brain structure might be used to predict treatment response. Multiple studies used structural MRI data to predict treatment outcome in OCD (e.g., ( Hashimoto et al, 2014 , Yun et al, 2015 )), but few studies examined neural biomarkers for treatment-resistant OCD ( Dunlop et al, 2016 , Van Laere et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since OCD has been associated with various structural brain abnormalities ( Boedhoe et al, 2017 , Gan et al, 2017 , Hashimoto et al, 2014 ), differences in (individual) brain structure might be used to predict treatment response. Multiple studies used structural MRI data to predict treatment outcome in OCD (e.g., ( Hashimoto et al, 2014 , Yun et al, 2015 )), but few studies examined neural biomarkers for treatment-resistant OCD ( Dunlop et al, 2016 , Van Laere et al, 2006 ). Nevertheless, the potential benefits of a reliable biomarker for DBS response are substantial.…”
Section: Introductionmentioning
confidence: 99%